The sound and function of different language particles in Zhuang songs of some western areas in Guangxi - Zhi, Lin; Musib, Ahmad Faudzi (Logos Verlag Berlin, 2024)
The often as ‘ornamental’ syllables named language elements refer to song-text particles, sometimes also named ‘vocables’, or appellations interspersed among the lyrics during the actual singing process of the singer. It appears to some extent in the Zhuang singer’s singing of songs in various regions. Unfortunately, these syllables are often overlooked in textual records because most of them cannot be interpreted in terms of their actual lexical meaning when they are independent of the wording of the phrase. The specific ex-pressions of the singers play an essential role and are an inseparable part of Zhuang songs. If the core text of the lyrics is like the beam of the house, then the vocables are the bricks of the wall. The combination of the two can build a house of Zhuang songs. Based on the audio data of Zhuang songs collected at the border and junction areas of some western areas in Guangxi, this study compares the difference between the song-book texts written by the singers that need a memory tool and the actual singing syllables used. For that, the authors interviewed the singers, analysing the changes produced in sound by the different language particles or short sentences in the singing process and summarizing their laws and functions within the singing events.